Optimizing Employee Performance: The Role of Work Discipline and Quality of Work Life in Enhancing Job Satisfaction - , Sumardin; , Sabri; Sidik, Muhammad; Arpah, M; Aras, Mohammad (Profesional Muda Cendekia Publishing, 2025)
Research Aims: This study analyses the impact of work discipline and quality of work life on employee performance, with job satisfaction as a mediating variable. Conducted in an industrial setting in Batamindo, it examines how compliance with organizational rules and work-life balance influence performance and satisfaction. Design/methodology/approach: Using a quantitative approach, data was collected through surveys from 100 employees selected via purposive sampling. Structural Equation Modelling (SEM) was used for regression and path analysis to assess direct and indirect relationships. Research Findings: Work discipline does not significantly impact employee performance or job satisfaction. However, quality of work life positively influences both job satisfaction and performance, with job satisfaction acting as a key mediator. Additionally, job satisfaction significantly improves employee performance, but it does not mediate the relationship between work discipline and performance. Theoretical Contribution/Originality: This study provides a comprehensive analysis of employee performance drivers, offering valuable insights for organizational policies, HR management, and future research.